Hubungan Pola Asuh Orang Tua Terhadap Perkembangan Kognitif Anak Usia Dini di TK Aisyiyah Bustanul Athfal Limpung Kabupaten Batang Tahun Ajaran 2015/2016 - Septiawati, Dewi; Drs Ilham Sunaryo, M.Pd.AUD, Drs Ilham Sunaryo, M.Pd.AUD (2016)
Democratic parenting is the best type of parenting style because it combines two types of extreme parenting which are both not really restrictive and not really free. Parents who implement this kind of parenting style have children whom become nice individuals. The charge of the household is still controled by the parents; however, the parents are very open to negotiate with the children. The children can still do things according to their will but it remains under the supervision of parents. Cognitive is an ability to think encompassing a simpler intellectual ability which involves memorizing, recalling, comprehending, assembling, knowing about the cause and effect, as well as to the ability to solve a problem that requires children for connecting and collaborating some ideas or methods learned to solve the problem, or the children find problem solving of the problem. The purpose of this study is to find out the correlation between parents' parenting styles and cognitive development of early children in TK Aisyiyah Bustanul Athfal Limpung, Batang Regency in academic year 2015/2016. This research is a descriptive research. It was conducted in TK Aisyiyah Bustanul Athfal Limpung, Batang Regency, in group A and B in academic year 2015/2016. The samples of this research were the kindergarten students in group A with the total number of 36 students and students in group B with the total number of 37 students. The total number of samples was 75 students. The technique used in taking sample was random sampling. The technique of analyzing data used in this research was Product Moment Correlations. The result of this research was that, there was a correlation between parents' parenting styles and cognitive development of early children in TK Aisyiyah Bustanul Athfal Limpung, Batang Regency in academic year 2015/2016. It could be proven by the result of r Pearson Correlation is 0,475 with a standard error of 5% rxy : rtabel = 0,475 : 0,296 to rxy > rtabel meant 0,475 > 0,76. With a standard error of 1% means rxy : rtabel = 0.475 : 0.227 to r xy > rtabel which means 0.475 > 0.2277 . Thus both the significance of 1 % or 5 % rxy > rtabel = 0.475 > 0.0296 > 0.227 indicating that Ho was rejected and Ha accepted meaning which meant that there was a correlation significance between parents' parenting styles and cognitive development of early children in TK Aisyiyah Bustanul Athfal Limpung, Batang Regency in academic year 2015/2016.